MODERN CRYPTOGRAPHIC TOOLS FOR DOING BUSINESS - Grebeniuk, Natalia; Dotsenko, Oleksii (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
Not much time has passed since the advent of the first Bitcoin cryptocurrency in 2009. It was the starting point for the development of blockchain technologies. In just one decade there occurred global rethinking of this significant technology for the economy. After a long stage of testing the mentioned technology reliability, it started to be tested in various fields of industry, logistics, e-commerce and business management. Cryptographic technology is a special case of using a decentralized data registry and a mechanism of decision making and coordination without human factor participation. Thanks to this range of properties, cryptographic technologies began to expand the field of their application, diversify functions and standards, and to improve their characteristics and qualities. Directly for business, it has truly become a technology of the future. Optimization and automation of business administration and management, logistics, expansion of methods of attracting investments – all this started to be subjected to cryptographic systems control. Cryptographic technologies cause more and more changes in the work of the financial sector that leads to finding new solutions in the field of state regulation of business processes. The article considers the use of such systems in business problems solving. Descriptions of the examples of the world experience in using cryptographic systems for optimization processes are given. The main types of tokens are compared, their operation and functions are described. The arguments for the most effective further expansion of the scope of using tokens are brought forward. The developed algorithm for the implementation of cryptographic technologies in business using the example of a blockchain platform is described.